School Well-being of Senior High School students in the Indonesian Region: A Review of the Literature - Hanny Mentari Putri*; Endah Kumala Dewi (Riwayat: Educational Journal of History and Humanities, 2023)
School is a place to gain knowledge, moral and character maturation, schools played a role in cognitive development, emotional and social development of individuals. Contentment, comfort and fulfillment of students' basic needs can be called school well-being. This article aims: (1) to review the meaning of school well-being and building aspects of student well-being, (2) identify factors to react of school well-being in Indonesia (3) and implications. This article reviews 7 research articles related to determinants of school well-being published in the last five years. The method used is a systematic literature review using the 2015 PRISMA guideline. The article search method was carried out by entering the keywords "school wellbeing" AND “school well-being”. The inclusion criteria for articles used are articles written in Bahasa and English, published in peer-reviewed journals, discussing school well-being senior high school, published between 2019-2023, and no cultural boundaries. There are 7 articles on school well-being senior high school in Indonesia.